Ten Interesting Facts about OnVac: A Tool to Learn Engineering and Technology Vocabulary - Zuraina, Ali; Suriya Kumar, Sinnadurai; Faridah, Hamzah; Ruhil Amal, Azmuddin; Nur Syafawati, Sabuan (Universiti Malaysia Pahang, 2014)
The purpose of this paper is to impart interesting facts about an online vocabulary game namely OnVac, which can be used to learn engineering and technology vocabulary. E-mail interviews conducted with 32 students on a voluntary basis in a public university in Malaysia revealed positive perceptions of OnVac as an interesting tool to learn engineering and technology vocabulary. It implied that online games such as OnVac could facilitate university students to enrich their engineering and technical vocabulary. Since the vocabularies are selected from their core engineering and technical reference books, it seemed that OnVac was able to facilitate the students in understanding of their core subjects better. The study also showed evidence that OnVac enabled them to retain the engineering and technology vocabulary for both short- and long-term recalls